A Study of Commercial Law (Economic Law) and Legal Politics Related to the Trade Practice of Adulterated Rice Circulating in the Community - Nomensen Freddy Siahaan; Agustina Wati; Ine Ventyrina (Journal of Social Research, 2025)
The National Police's Food Crime Investigation Task Force (Satgas) has named three suspects in the case of alleged production and circulation of premium rice not in accordance with quality standards by PT Padi Internasional Makmur (PT PIM) which markets the Sania, Fortune, Sovia, and Siip brands. The determination of suspects was carried out after examining witnesses, experts, and laboratory tests that showed violations in the production and packaging process. Coordinating Minister for Food Affairs Zulkifli Hasan emphasized that the government responded to this case with a plan to eliminate the classification of premium and medium rice, so that only two categories remained, namely ordinary rice and special rice with certain permits such as Pandan Wangi, Basmati, and Japonica. This study uses normative legal research methods through the analysis of law, jurisprudence, and legal doctrine, especially related to commercial law and political law. According to the author, the practice of oplosan rice has an impact on the community's economy and has the potential to increase poverty rates, as revealed by the Central Statistics Agency. Facts on the ground show the weak quality control at PT PIM, with only one certified officer out of 22 employees. For his actions, the suspect can be charged with the Consumer Protection Law and the Money Laundering Law with the threat of severe punishment. This case shows that the circulation of oplosan rice threatens legal certainty, justice, and community welfare, and causes unrest because the rice consumed is not in accordance with quality standards